2005
DOI: 10.1007/s00198-005-1974-5
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of hip fracture in Tottori Prefecture, Japan: Trend from 1986 to 2001

Abstract: We conducted a survey of all hip fractures in patients 35 years old and over during 1998-2001 in Tottori Prefecture, Japan, and compared them with those reported previously. The survey found 604, 671, 710, 729 patients, in 1998, 1999, 2000, and 2001, respectively. The mean age- and gender-specific incidences (per 100,000 person-years) for men were 108.0, 209.0, 449.1, and 780.0 in the age groups of 70-74, 75-79, 80-84 and over 84, respectively, and those for women were 249.1, 505.8, 1,115.4, and 2,066.4, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 36 publications
7
59
1
2
Order By: Relevance
“…(12) To compare the overall rates of hip fractures in women and men in Beijing to the rates in other countries we also standardized the rates for other selected countries to the 2004 US Census where reports provided sufficient data. (9,10,(12)(13)(14)(15)(16)(17)(18)(19) Results (Fig. 2).…”
Section: Analysesmentioning
confidence: 99%
“…(12) To compare the overall rates of hip fractures in women and men in Beijing to the rates in other countries we also standardized the rates for other selected countries to the 2004 US Census where reports provided sufficient data. (9,10,(12)(13)(14)(15)(16)(17)(18)(19) Results (Fig. 2).…”
Section: Analysesmentioning
confidence: 99%
“…(1,2) The number of osteoporotic fractures in Japan has been increasing as its society ages. (3,4) Osteoporotic fractures are associated with increased morbidity and mortality, and impose a huge financial burden on healthcare systems. (5)(6)(7) Preventing osteoporotic fractures in the elderly therefore represents an important issue in health economics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence and incidence of vertebral fracture in Japan are higher than those in the United States and Europe, (15,16) the incidence rate of hip fracture, which may cause a greater burden than other osteoporotic fractures, is lower in Japan compared to Western countries. (3,17) Here we estimated the cost-effectiveness of alendronate therapy to prevent fractures in postmenopausal Japanese women who have low bone mineral density (BMD) but do not have osteoporosis or a history of fracture. Because the FRAX algorithm is not open to the public, we performed a model-based, costeffectiveness analysis that considered age, BMD, and the presence of clinical risk factors by using published sources.…”
Section: Introductionmentioning
confidence: 99%
“…Hagino et al reported that the incidence of hip fracture has been increasing in elderly women in Japan 2) . The prevention of hip fractures is important for maintaining independence of activities of daily living (ADL) and quality of life for elderly Japanese women, and the appropriate assessment of bone strength and physical function is necessary for the prevention of hip fracture.…”
Section: Introductionmentioning
confidence: 99%